PEMALSUAN DOKUMEN DALAM PENDAFTARAN HAK ATAS TANAH DI DENPASAR - I Gede Somonita; I Made Suwitra; I Made Sepud (Jurnal Hukum Prasada, 2017)
ABSTRACT Legal documents in the transactional process of land ownership transition are often neglected by parties in the registration of land ownership rights in Denpasar. This thesis discusses 2 matters which consists of the following ones : first, what the criminal responsibility in the document fraud towards the registration of land ownership rights is and secondly concerning what the legal protection for the land certificate holder in the registration of which contains fraudulent documents is. The findings are as follow. First, the criminal responsibility of the document fraud towards the registration of land ownership is the policy of case criminalization of criminal acts in the laws of land as based on criminal law which upholds the concept of being against the material law, in the sense that the criminal act is not only an act being against the written laws alone but also is an act being against unwritten laws. The reason for exception of such an action has to be based on written laws and unwritten laws in order for the legal certainty to be achieved. Second, legal protection for the land certificate holder in the registration process of which has fraudulent documents, the responsibility of the national land agency, who produces the products. In getting the firm legal certainty for certificate products which are issued as evidences of land ownership in Indonesia, it is also required to have legal certainty and legal protection in order to assure ownership of the citizens. Key words: Fraud, Document, Land Ownership Right Registration.